Alcohol Consumption and Alcohol-related Mortality in Canada, 1950–2000 - Ramstedt, Mats (Can J Public Health, 2004)
OBJECTIVE: To describe trends in overall alcohol consumption and alcohol-related mortality in Canada, and to test regional associations between per capita alcohol consumption and alcohol-related mortality. METHOD: Alcohol sales for 1950–2000 were used to measure total alcohol consumption; alcohol-related mortality consisted of nine different alcohol-related causes of death for 1950–1998. Alcohol consumption and alcohol-related mortality were described for 1950–2000, and measures of dispersion were calculated to assess the homogeneity across regions. FINDINGS: Both alcohol consumption and alcohol-related mortality increased in all regions up to 1975–80 and then underwent a decline until the 1990s. Since 1996, consumption began to increase. Beer represented more than half of the total consumption throughout the study period, although overall, the share of wine increased, particularly in the larger provinces. Over time there have been fewer differences in per capita consumption and alcohol-related mortality rates across the regions. A strong positive cross-regional relationship was observed between explicitly alcohol-related mortality and per capita consumption, whereas cirrhosis showed only a weak geographical association with consumption. CONCLUSIONS: Since 1950, there has been a general trend toward national homogenization, especially with respect to drinking levels but also to alcohol-related mortality. A strikingly close regional relationship between alcohol consumption and alcohol-related mortality suggests that consumption is an important marker of alcohol-related harm in Canada.